’The Country Mouse at Play’: Theatre in the Peace River District 1914-1945 - Day, Moira (Theatre Research in Canada / Recherches théâtrales au Canada, 1991)
Most theatre history studies concentrate on theatre as it was experienced in the larger urban centres of eastern and western Canada assuming that theatre in the rural districts either followed a similar pattern or simply did not exist. By exploring the dynamics of entertainment in the prosperous but unusually isolated Peace River country in northwestern Alberta between 1914 and 1945, this paper hopes to suggest that rural theatre, particularly in the more isolated districts, often had a distinct character of its own arising from the particular geography, social needs, economic conditions and human resources of the area. La plupart des études de l’histoire du théâtre traitent de l’expérience théâtrale dans les plus grands centres urbains de l’ouest et de l’est canadiens, en supposant que le théâtre dans les districts ruraux suivait un modèle similaire ou tout simplement n’existait pas. Au moyen d’un examen des dynamiques du spectacle dans le district de Peace River dans l’Alberta du nord-ouest - un groupe de communautés prospères mais extraordinairement isolés - entre 1914 et 1945, cet article suggère que l’expérience rurale du théâtre, particulièrement dans les districts isolés, avait souvent un caractère distinct provenant de la géographie, des besoins sociaux, des conditions économiques, et des ressources humaines de la région.